Performances of concrete with binder and/or aggregates replacement by all-solid waste materials - Wang, Jixiang; Ren, Caifu; Huang, Tianyong; Li, Xiang; Cao, Wanlin; Zhu, Yingcan; Wei, Peng; Wang, Dongmin; Liu, Ze (Journal of cleaner production, 2024)
Aiming for an all-solid waste concrete, a quaternary solid waste binder (SWBs) system comprising blast furnace slag, fly ash, desulfurization gypsum, and Bayer red mud was developed and utilized for both binders and preparation of cold bonded artificial aggregates. The first section investigated and discussed the hydration properties and strength gain mechanism of SWBs, revealing that ettringite formation and growth contribute to early age strength development of SWBs, while C-A-S-H formation contributes significantly to the later strength gain. The second section systematically studied the concrete performances, including mechanical properties, shrinkage, chlorides, and seawater resistance. An all-solid waste-based concrete strategy was presented by gradually substituting cement and natural aggregates. It was observed that SWBs-based concrete exhibited significantly lower shrinkage and excellent chloride ion resistance, although slightly lower mechanical properties were observed. The solid waste-based artificial aggregates proved viable alternatives to natural rock aggregates in low-strength concrete classes. Incorporating artificial aggregates endowed the concrete with self-curing properties and reduced its shrinkage and chloride migration, with only a minor effect on its mechanical strength. Lastly, an all-solid waste concrete combining the characteristics of SWBs and cold-bonded artificial aggregates was achieved. The resulting concrete exhibited lower shrinkage and excellent chloride and seawater resistance. This study provides a reference for designing and developing solid waste-based binders and concrete. [Display omitted]